A contribution to the studies of households in Costa Rica - Carballo Murillo, Natalia (2023)
This article aims to contribute to the investigations of households in Costa Rica. For this, the changes in Costa Rican households will be explained from secondary sources, and through interviews, a reconstruction of the types of households of three generations of families will be made. One interview was conducted per generation, for a total of fifteen interviews. The information obtained in the interviews was analyzed with the computer program Atlas.ti. The first generation of women started their families in nuclear homes, in charge of making economic decisions, and even though, in some cases, upbringing and household decisions regarding their sons and daughters were shared, education fell in them. In the case of the types of households of second-generation women, at the time of the interviews, they are extended, compound, and conjugal households with children and without children. While the homes of third-generation people, who are outside their mothers' homes, are single-parent, composed, or renting an apartment with "roomies". Regardless of the generation, the transformation of the home is the result of the growth of the initial group and the aging of its members, but also of the economic situations that each of the families is going through. These economic situations change over time and depend on the economic context of the country, and the socioeconomic tools of the group, such as the level of schooling and the head of the household.